Abnormal postprandial duodenal chyme transport in patients with long standing insulin dependent diabetes mellitus. Issue 5 (1st November 1997) - Nguyen, H N; Silny, J; Wüller, S; Marschall, H-U; Rau, G; Matern, S
Abstract : A bstract Background —Patients with long standing diabetes mellitus frequently have upper gut dysmotility. Gastroparesis has been well studied, whereas detailed data on duodenal motor function are limited. Aims — To characterise postprandial duodenal chyme transport in such patients. Methods — Intraluminal multiple impedance measurement, recently introduced as a novel technique for investigation of chyme transport, was used to study postprandial duodenal chyme flow in 10 patients with long standing insulin dependent diabetes mellitus with gastroparesis, and 10 healthy volunteers. Results— Four distinct transport patterns of chyme, termed bolus transport events (BTEs), were found in both groups and could be characterised as: short distance propulsive; simple long distance propulsive; retrograde; and complex long distance propulsive. Diabetic patients had significantly lower numbers of propulsive BTEs (p<0.01), and higher proportions of retrograde BTEs and complex long distance BTEs (p<0.05) than control subjects, whereas the proportion of simple long distance BTEs was significantly lower (p<0.05). The mean propagation velocities of the BTEs were similar in both groups. Conclusion— Abnormal postprandial duodenal chyme transport was found in patients with long standing insulin dependent diabetes mellitus. This is characterised by transport disorganisation and may result in disturbed chyme clearance.